The Existence of Qanun Jinayat: Legislative Efforts to Integrate Islamic Law into National Law - Fauzi, Muhammad Rusydan; Wijaya, Putra Arya; Yuniarsih, Rina Isti; Najmudin, Deden (As-Siyasi: Journal of Constitutional Law, 2024)
Islamic law, derived from the teachings of the Qur'an and Hadith, plays a significant role in various countries with a majority Muslim population. Indonesia, the country with the largest Muslim population in the world, has experienced fluctuations in the integration of Islamic law within its national legal system. This dynamic has led to the legislative incorporation of Islamic law into the national legal framework as an expression of religious obedience in fulfilling the principles of Sharia. This legislative effort is manifested in Aceh's Qanun Jinayat, implemented in the Nanggroe Aceh Darussalam Province. This study aims to examine the existence of Aceh's Qanun Jinayat within the national legal system following the legislative integration of Islamic law. This research employs a normative legal approach, utilizing juridical-normative methods, with data collection based on the study of primary, secondary, and tertiary legal materials. The findings of this study indicate that the existence and implementation of the Qanun Jinayat in Aceh aim to preserve security and welfare as stipulated in the Aceh Qanun Jinayat. This is mainly due to the Islamic law legislation framework, which grants the Nanggroe Aceh Darussalam Province the authority to apply Islamic legal principles through regional autonomy.